International finance : a practical perspective - Buckley, Adrian , 1944- (Pearson, 2012)
International Finance is a complete and authoritative text on the theory and practice of finance in the international arena. The book offers a user-friendly, European orientated, approach to this sometimes complex topic and moves from the basics to the advanced with clarity and conciseness